Term Pregnancy at the Site of Atresia Following Vaginal Canalization in a Case of Uterus Didelphys with Hemivaginal Atresia and Ipsilateral Renal Agenesis - Fang-Ping Chen; Koon-Kwan Ng (Elsevier, 2006)
Objective: Uterus didelphys with hemivaginal atresia and ipsilateral renal agenesis is a rare syndrome of müllerian anomalies. Term pregnancy at the site of atresia is even rarer. Case Report: A 28-year-old married woman presented with menometrorrhagia and primary infertility. Pelvic examination led to the suspicion of a pelvic mass between the uterus and bladder, and protruding to the right site of the paracervix. Ultrasound and magnetic resonance imaging examination revealed a left ovarian teratoma, right hematocolpos, and uterus didelphys with atresia of the right vagina and ipsilateral renal agenesis. Enucleation of the left ovarian teratoma by laparoscopy and drainage of hematocolpos by 2-cm canalization as a marsupialization procedure at the right paracervical protruding part under sonographic guidance were performed. Thereafter, a term pregnancy in the affected side was achieved. The patient underwent cesarean section due to breech presentation. Conclusion: A greater awareness of the syndrome of uterus didelphys, hemivaginal atresia, and ipsilateral renal agenesis should lead to a correct diagnosis. We herein report our experience with the correct diagnosis and alternative management of this rare syndrome.